Analysis of Experiential Marketing Effect on Tourist Satisfaction Levels at The Tourist Restaurant in Belitung District - Pelliyezer Karo Karo (STIEPAR YAPARI Bandung, 2020)
This study is to determine the effect of experiential marketing on the level of tourist satisfaction in tourist restaurants in Belitung Regency. Experiential marketing that was studied included the variables of sense, feel, think, act and relate. Data collection techniques used were interviews, questionnaires, and observations. The data analysis model used is multiple linear regression analysis with hypothesis testing carried out simultaneously and partially. Research on 115 samples shows that independent variables consisting of sense, feel, think, act and relate simultaneously have a very strong influence on the dependent variable tourist satisfaction level. While partially, the study produced that there are three variables namely feel, act and relate which have a significant influence on the level of tourist satisfaction, where the feel variable is the most dominant.